Hepatocellular Carcinoma with Portal Vein Tumor Involvement: Best Management Strategies - Liu, Po-Hong; Huo, Teh-Ia; Miksad, Rebecca A. (Seminars in Liver Disease, 2018)
Portal vein tumor thrombosis (PVTT) commonly occurs in patients with hepatocellular carcinoma (HCC). Patients with PVTT usually have an aggressive disease course, decreased liver function reserve, limited treatment options, higher recurrence rates after treatment, and, therefore, worse overall survival. Among untreated HCC patients with PVTT, the median overall survival has been reported as low as 2 to 4 months. Historically, many aspects of PVTT have impacted the theoretical and practical safety and efficacy of treatment, for example, disordered blood flow and associated impairment of liver function, heat-sink effects of blood flow in the area of the PVTT, and risk of recurrence due to tumor location in the blood vessel. The current Barcelona Clinic Liver Cancer staging system categorizes HCC patients with PVTT as advanced stage, for which the standard of care is targeted therapy with sorafenib. However, sorafenib is associated with only marginal benefits among patients with PVTT. First-line lenvatinib, which was shown to be noninferior to sorafenib, excluded patients with main portal trunk invasion. Regorafenib and nivolumab, an immune-based therapy, were recently approved in the United States for second-line therapy after sorafenib. Preliminary results for cabozantinib suggest a benefit in the second-/third-line after sorafenib failure. In addition, rapid advances in many fields (surgery, interventional radiology, nuclear medicine, and immunotherapy) have increased the potential treatment options for the management of this complex disease entity. A large portion of the emerging evidence focuses on the broader category of advanced HCC of which PVTT is a subgroup. While many of these studies show promising results, the efficacy among PVTT patients requires validation in prospective studies. Real-world data may help fill the evidence gap for patients not eligible for clinical trials due to common hepatic function requirements. The variety of new treatment advances for the heterogeneous and complex disease entity of HCC with PVTT means that personalized, multidisciplinary management may be necessary to achieve optimal outcomes. In this narrative review, we summarize the evolving management strategies for patients with HCC and PVTT.
Keywords: portal vein tumor thrombosis; advanced hepatocellular carcinoma; locoregional treatment; immunotherapy; real-world data